2011
DOI: 10.1093/aje/kwr011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Small Class Sizes on Mortality Through Age 29 Years: Evidence From a Multicenter Randomized Controlled Trial

Abstract: Limiting the number of students per classroom in the early years has been shown to improve educational outcomes. Improved education is, in turn, hypothesized to improve health. The authors examined whether smaller class sizes affect mortality through age 29 years and whether cognitive factors play a role. They used data from the Project Student Teacher Achievement Ratio, a 4-year multicenter randomized controlled trial of reduced class sizes in Tennessee involving 11,601 students between 1985 and 1989. Childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
0
25
1
Order By: Relevance
“…In both the short-and long-term, small classes (<20 pupils) in the first three grades have been found to have a positive effect on pupil outcomes such as academic achievement, referrals to special education, and discipline problems (11,12). Studies on the benefits of reduced class sizes for pupils' health have shown mixed findings (13), and the health benefits of reduced class sizes for teachers are unknown. However, general education teachers indicate that they would have more positive attitudes towards the inclusion of SEN pupils if class sizes were reduced to 20 pupils (14).…”
mentioning
confidence: 99%
“…In both the short-and long-term, small classes (<20 pupils) in the first three grades have been found to have a positive effect on pupil outcomes such as academic achievement, referrals to special education, and discipline problems (11,12). Studies on the benefits of reduced class sizes for pupils' health have shown mixed findings (13), and the health benefits of reduced class sizes for teachers are unknown. However, general education teachers indicate that they would have more positive attitudes towards the inclusion of SEN pupils if class sizes were reduced to 20 pupils (14).…”
mentioning
confidence: 99%
“…The differing results of Chetty et al (2011) and Dynarski et al (2013) may result from the latter's longer follow-up period; that is, age 27 may be too early to determine the positive effects of CSR; one could detect this sign in Wilde et al's (2011) intermediate results. Muennig, Johnson, and Wilde (2011) investigated another effect of small class sizemortality. Intuitively, small class size would reduce mortality if it indeed contributed to the improvement of the cognitive and noncognitive skills of the treated.…”
Section: Long-term Effectsmentioning
confidence: 99%
“…On the other hand, if the treatment enhanced one aspect of noncognitive skills that might increase mortality rates, the treatment group would be more likely to die than the control group. According to Muennig et al (2011), 141 of 11,240 students died by 2007, and students assigned to small classes showed significantly higher mortality, with a hazard ratio of 1.58. Because inadequate firearms and automobile safety were the two leading causes of death among STAR participants, Muennig et al (2011) speculated that the treatment might have boosted exploration and extroversion, which could lead to higher mortality.…”
Section: Long-term Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller class sizes and lower numbers of students per teacher, i.e., smaller student-teacher ratio are examples of learning environment characteristics that are typically refl ective of greater school fi nancial resources. In the USA, small class sizes in the early grades (1-3) were shown to be associated with better cognitive capacity and academic achievement among the students, but the effects on health were mixed (Muennig, Johnson, & Wilde, 2011 ;Muennig & Woolf, 2007 ). A Finnish study took into account student characteristics (proportion of students with special educational needs) and found that the risk for teacher sick leave increased with the percentage of students with special educational needs, and this association was stronger in schools with a high student-teacher ratio (Ervasti et al, 2012 ).…”
Section: Financial Capital and Human Capital In Schoolmentioning
confidence: 99%